Optimization of Probiotic Addition in Feed on Growth of Baung Fish (Hemibagrus nemurus) - Sri Sri; Agus Setiawan; Sarmila Sarmila (Journal of Aquaculture Science, 2021)
Baung fish is one type of local fish that has a slow growth. One of the efforts to increase the growth of baung fish can be done by using probiotics. This study aimed to determine the optimum dose of probiotic addition for the baung fish rearing. The experiment used a completely randomized design (CRD) with four treatments, three replications, and one control. The probiotic doses: 2 ml/kg of feed (A), 4 ml/kg of feed (B), 6 ml/kg of feed (C), 8 ml/kg of feed (D) and 0 ml/kg of feed (control) were used as treatment. The commercial feed was given ad satiation with a frequency of feeding three times a day. Observations were made for two months. The results showed that the D treatment of 8 ml/kg of feed gave the best absolute weight growth and feed conversion ratio. While, the baung fish survival rate was not significantly different on all treatments.Keywords: Baung fish, growth, probiotics